INFLUENCE OF BODY IMAGE AND SELF-CONFIDENCE ON PUBLIC SPEAKING SKILLS STUDENT - Muhamad Supian (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2022)
This study aims to determine the influence of body image and self-confidence on public speaking skills in students of the Economic Education Study Program at STKIP Muhammadiyah Sampit for the 2021/2022 Academic Year. The population in this study was students in semesters 2, 4, 6 and 8 of the Economic Education Study Program at STKIP Muhammadiyah Sampit which amounted to 122 students , which was then taken by 32 students as a sample in this study. The data analysis technique used is a multiple linear regression analysis technique. The results of the analysis show that the influence of body image and self-confidence on public speaking ability in students of the economic education study program at STKIP Muhammadiyah Sampit for the 2021/2022 academic year is 0.587 or 5.87% shown in the Adjusted R Square value. The value explains that the variation or ups and downs of variables bound by public speaking ability (Y) are influenced by free variables or body image (X1) and confidence (X2) by 5.87%. While the remaining 94.13% is explained by other variables that were not studied in this study .